Developing a Model for Selecting Smart Contractors - Al Nabulsi, Maryam Wasef (2021)
A Master of Science thesis in Civil Engineering by Maryam Wasef Al Nabulsi entitled, “Developing a Model for Selecting Smart Contractors”, submitted in May 2021. Thesis advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).